Enhancing Christian Theological Education Effectiveness in Urban Indonesian Contexts - Onibala, Ronald Stevly; Rindu, Kiem (Scriptura Indonesia, 2024)
This qualitative research investigates Christian education effectiveness in Bekasi City through a comprehensive analysis of perspectives from priests, pastors, theological educators, and church workers. The study employs semi-structured interviews with ten key stakeholders to examine current pedagogical approaches, identify gaps between theological preparation and practical ministry demands, and develop evidence-based enhancement recommendations. Findings reveal substantial institutional capacity for adaptation with significant opportunities for systematic improvement through community partnership development, professional development program establishment, and pedagogical innovation expansion. The research demonstrates that effective Christian education enhancement requires strategic attention to collaborative frameworks rather than fundamental institutional transformation. Community engagement emerges as the highest-impact improvement opportunity, while technology integration and leadership development represent critical enhancement priorities. The study contributes valuable insights regarding contextually appropriate theological education in Southeast Asian urban environments while providing transferable frameworks for Christian educational institution development in diverse cultural contexts. Results indicate optimistic potential for systematic educational enhancement through coordinated development initiatives that build upon existing institutional strengths while addressing identified capacity gaps. The research provides evidence-based guidance for theological education improvement that maintains theological integrity while enhancing practical ministry preparation effectiveness.